# Answer to Question #14627 in Trigonometry for Danielle

Question #14627

Simplify:

2x^2y^4*4x^2y^4*3x

------------------------

3x^-3y^-2

2x^2y^4*4x^2y^4*3x

------------------------

3x^-3y^-2

Expert's answer

2x^2y^4 * 4x^2y^4 * 3x

---------------------------- =

3x^-3y^-2

2 * x^2y^4 * 4 * x^2y^4 * 3 * x

= ------------------------------------ =

3 * x^-3y^-2

8 * x^2y^4 * x^2y^4 * x

= --------------------------- =

x^-3y^-2

8 * x^(4y^4 + 1)

= ------------------- = 8 * x^(4y^4 + 3y^2 + 1)

x^-3y^-2

---------------------------- =

3x^-3y^-2

2 * x^2y^4 * 4 * x^2y^4 * 3 * x

= ------------------------------------ =

3 * x^-3y^-2

8 * x^2y^4 * x^2y^4 * x

= --------------------------- =

x^-3y^-2

8 * x^(4y^4 + 1)

= ------------------- = 8 * x^(4y^4 + 3y^2 + 1)

x^-3y^-2

## Comments

## Leave a comment